(untitled) - Fukunaga, Keinosuke (New York, 1972)
This completely revised second edition presents an introduction to statistical pattern recognition. Pattern recognition in general covers a wide range of problems: it is applied to engineering problems, such as character readers and wave form analysis as well as to brain modeling in biology and psychology. Statistical decision and estimation, which are the main subjects of this book, are regarded as fundamental to the study of pattern recognition. This book is appropriate as a text for introductory courses in pattern recognition and as a reference book for workers in the field. Each chapter contains computer projects as well as exercises.
Keywords: Pattern perception,Decision making,Nhận định Pattern,Đưa ra quyết định; Statistical methods,Mathematical models,Phương pháp thống kê,Mô hình toán